Bio-composites treatment for mitigation of current-induced riverbank soil erosion - Dubey, Anant Aishwarya; Ravi, K.; Shahin, Mohamed; Dhami, Navdeep; Mukherjee, Abhijit (ELSEVIER, 2021)
Mitigation of erosion along the riverbanks is a global challenge. Stabilisers such as cement can control erosion, but it risks the river ecology. This paper presents the erosion characteristics of riverbank soil treated with two biological stabilisers that alleviate the ecological cost. The riverbank soil of one of the largest river systems, Brahmaputra, is treated by bio-polymeric and bio-cement binders and their composite. Moreover, a novel selective bio-stimulation technique has been employed to achieve bio-mineralisation. The soil stabilisation is assessed by needle penetration tests and CaCO3 contents. The specimens were tested in a flow-controlled hydraulic flume subjected to a critical current profile ranging from 0.06 to 0.62 m/s. Soil samples treated up to four cycles of biocementation have been tested at three different slopes (30°, 45° and 53°). The eroded depth and erosion rate are evaluated with image analysis. Up to four-fold reduction in the erosion rate was observed with biocementation treatment. However, cementation beyond a threshold led to the formation of brittle chunks. A bio-composite was devised through a pre-treatment of low-viscosity biopolymer along with biocementation. The bio-composite was found to effectively mitigate the current-induced erosion with 36% lower ammonia production than the equally erosion resistant biocemented counterpart. The dual characteristics of the bio-composite were confirmed with the microstructural analysis. This study unravels the potential of biopolymer-biocement composite as a sustainable erosion mitigation strategy.